NILAI MORAL PADA TOKOH SELENA DALAM NOVEL SELENA KARYA TERE LIYE - Uli Wahyuni; Yosi Pratiwi (Universitas Batanghari, 2022)
This research was motivated by finding moral values in Tere Liye's Selena Novel. This study aims to describe the moral values of Selena in Tere Liye's Selena Novel. This research uses descriptive, qualitative methods, namely describing moral values. This research data is in the form of findings related to five aspects of moral values including; help each other, politeness, obedient, self-control and trust contained in selena’s character. The data are analyzed based on the existing theories in the literature study that the author makes as the theoretical basis in analyzing this research. This type of qualitative descriptive research is used as a way to describe the moral value contained in Selena in Tere Liye's Selena Novel. The results of this research can be described by the author that Selena's character contains moral values from aspects of moral values including; help each other, politeness, obedient, self-control and trust. The number of findings used as data in the form of quotations about moral values is as many as 52 citations. From the results of this study, it can be described that Selena's novel by Tere Liye contains moral values that can be used as reading material for the community as well as learning materials in schools.